2012
DOI: 10.1186/1472-6939-13-19
|View full text |Cite
|
Sign up to set email alerts
|

"It's for a good cause, isn't it?" - Exploring views of South African TB research participants on sample storage and re-use

Abstract: BackgroundThe banking of biological samples raises a number of ethical issues in relation to the storage, export and re-use of samples. Whilst there is a growing body of literature exploring participant perspectives in North America and Europe, hardly any studies have been reported in Africa. This is problematic in particular in light of the growing amount of research taking place in Africa, and with the rise of biobanking practices also on the African continent. In order to investigate the perspectives of Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 15 publications
3
29
1
Order By: Relevance
“…10 Similar to this study, other researchers have found that altruism (wanting to help others), detachment from the tissue (''it's out anyway''), and seeing research as ''a good cause'' were reasons given for agreeing to donate. 10,15 Patients perceive the physician as a key messenger, and this is not surprising. A growing body of literature points to the significance of the ''physician ask'' in enrolling patients in clinical trials and other research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similar to this study, other researchers have found that altruism (wanting to help others), detachment from the tissue (''it's out anyway''), and seeing research as ''a good cause'' were reasons given for agreeing to donate. 10,15 Patients perceive the physician as a key messenger, and this is not surprising. A growing body of literature points to the significance of the ''physician ask'' in enrolling patients in clinical trials and other research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, few studies have explored if there are racial and ethnic, or other demographic differences in acceptance of a given consent model. 17 Acceptance of informed consent models for biobank research has received significant international attention, [18][19][20][21] but limited focus in the US. Additionally, the results of studies on the public's acceptance of the various consent models used and proposed for biobank research has been conflicting and variably received.…”
Section: Introductionmentioning
confidence: 99%
“…They found evidence to support earlier work that indicated that this could be justified provided that researchers were trustworthy, the research was accompanied by community engagement, and that appropriate governance structures were in place [78]. They also identified a concern that revisiting participants for reconsent for each new study was impractical.…”
Section: Discussionmentioning
confidence: 63%